Cultural diversity in education: theoretical reflections on the treatment of culture in the classroom - Vitorino, Diego da Costa (Faculdade de Ciências e Letras - Unesp - Araraquara., 2012)
Think of a pre-university courses. Despite being cram something so commonplace in the lives of Brazilian students who intend to enter into public and private universities, the analysis showed that they are the stage of the race read less population policy to achieve the university seats. The paper presents the political-pedagogical proposal of pre-university courses for Blacks and Needy” drawn up by teachers and coordinators of the ONG FONTE, whose main goal is the inclusion of this population in higher education. The research reveals that the training of educators to work with the issue of combating racism, ends up creating an anti-racist pedagogy, paying close attention to discrimination and prejudice in the classroom. The research is important to emphasize the fact that the association between government and civil society in developing local policies of affirmative action in order to implement the law 10.639/03 within their educational projects.